Dementia in the old age: a gloomy wood later in life - Virginia Boccardi; Lucia Paolacci; Patrizia Mecocci (Geriatric Care, 2018)
Dementia incidence is growing at an impressive rate worldwide, mostly affecting old age subjects. Looking and considering the disease as the same in younger adult does not seem the successful way to find a proper solution regarding prevention and therapy this since there are too many differences between these two forms from biological to clinical aspects. Three question arises from a deep reflection on dementia in the oldest old: i) if it is a continuum with physiological brain aging; ii) what are the linking mechanisms underlining the disease and brain normal aging; iii) if or how it is possible to prevent or manage the disease differently in this population. We strongly believe that dementia is not an inevitable result of ageing, but when it appears in the oldest olds, it assumes distinctive characteristics of a geriatric syndrome where etiology, pathogenesis, clinical manifestations, course of the disease and management require a patient-tailored approach that can not be separated from a careful multidimensional evaluation.